Assessing the Impact of Post-Release Community Supervision on Post-Release Recidivism and Employment, United States, 2004-2011 - Bales, Bill ([Verlag nicht ermittelbar], 2021)
This study sought to examine the effect of of two separate forms of post-prison supervision on offender recidivism and employment outcomes: split supervision and conditional release supervision. In order to assess the effect of post-prison supervision on reentry outcomes for Florida inmates, this study addressed the following research questions: What is the impact of post-release supervision on employment and recidivism? Do various types of post-release supervision result in different outcomes of employment and recidivism? How does the length of post-release supervision impact employment and recidivism? Florida was chosen as the state of focus because of its shift from indeterminate to determinate sentencing and elimination of parole in the 1980s. Researchers used arrest data, corrections data, and employment data from the Federal Department of Corrections, the Florida Department of Law Enforcement, and the Florida Department of Revenue.